Constructing Marxist ethics : critique, normativity, praxis - Thompson, Michael J., 1973- (Studies in critical social sciences, 2015)
Constructing Marxist Ethics offers a series of compelling essays that reassess the role of ethics and moral values in Marxist theory and philosophy.